Absorptive Capacity in Practice-Based Innovation Activities: the Case of Lahti Region, Finland - Anne Paalanen; Vesa Harmaakorpi; Timo Pihkala (European Regional Science Association (ERSA), 2006)
As a consequence of for example agglomeration economies, features such as good reputation and highly-skilled labour force tend to accumulate in university regions. The accumulation of highly-skilled labour and high research intensity secure a continuous flow of "raw-material" for innovations in the knowledge-based economy. However, in the regions lacking a university it is vitally important to find other ways of increasing innovation activity. Through implementation of non-linear innovation activity which combines knowledge of normal practice-based activities and science-based research, a region can create radically new perspectives of operating. The new theories of innovation suggest that a great potential of innovation exists in the structural holes and weak links of the innovation system. The new sources of innovation set demands for the innovating partners. In order to exploit the hidden potential in the innovation system the actors of the region must possess, for example, high absorptive capacity, tolerance for diversification and especially the bridging elements of social capital. The Lahti Region in Finland is one of the regions lacking strong regional research base. Determined to create a new source of competitive advantage, the Lahti Region is heading towards a vision of being a top region in promoting practice-based innovation activities. Therefore, the region has created a new policy framework to achieve the vision: network-facilitating innovation policy. The policy aims to promote networked innovation processes especially by exploiting the potential of the structural holes of the innovation system and linking the research-based knowledge from neighbouring strong research centres in the regional innovation processes. This paper examines the readiness of the regional actors to face the demands of the new policy framework. The case study is a compilation of 12 interviews of the key persons in the regional development field and a survey study among representatives of companies, educational and research organizations as well as public organizations.
Keywords: 330